Arketamine: a scoping review of its use in humans - Leal, Gustavo C.; Lima-Araújo, Isabel; Roiter, David G.; Caliman-Fontes, Ana Teresa; Mello, Rodrigo P.; Kapczinski, Flávio; Lacerda, Acioly L. T.; Quarantini, Lucas C. (European archives of psychiatry and clinical neuroscience, 2025)
Arketamine (R-ketamine), an enantiomer of ketamine, has historically been less studied than esketamine (S-ketamine) and the racemic mixture. Recent preclinical studies suggest that arketamine may offer prolonged antidepressant effects and a superior safety profile. This scoping review aims to assess and synthesise existing literature on the clinical use of arketamine in humans. This review follows the PRISMA for Scoping Reviews guidelines, with a comprehensive search conducted in PubMed, Embase, ClinicalTrials.gov, and the WHO International Clinical Trials Registry. Eligible studies included those reporting the administration of arketamine to humans. Data were extracted and synthesised descriptively. A total of 20 studies involving 410 subjects were included. Arketamine was primarily investigated for pain management and depression. While early evidence suggests arketamine may be effective in reducing pain, most studies were small and conducted in non-clinical settings. In psychiatry, trials indicate potential antidepressant effects, but results are inconsistent, and some studies remain unpublished. A consistent observation across most studies is arketamine’s favourable safety profile, showing lower incidences of dissociative and psychotomimetic effects compared to esketamine and racemic ketamine. Arketamine may have a role in pain management and psychiatry, with a favourable safety profile compared to other forms of ketamine. However, the small scale of many studies limits the generalizability of findings, and results in depression trials are mixed. Larger, well-designed studies, possibly with higher doses, are needed to determine its therapeutic potential and establish its place in clinical practice.